The downside of downregulation - Gründer, Gerhard; Cumming, Paul (Brain, 2019)
This scientific commentary refers to ‘Reduced striatal dopamine synthesis capacity in patients with schizophrenia during remission of positive symptoms’, by Avram et al.(doi:10.1093/brain/awz093).